Mechanisms for Interpretative Cooperation: Fan Theories in Virtual Communities - Amo, José Manuel de; García-Roca, Anastasio (Frontiers in Psychology, 2021)
This work focuses on analyzing fan theories as interpretive processes shared by users of virtual reading communities. Within these spaces of participatory culture, a complex strategy of interactions among its members is encouraged to formulate conjectures about the text's intentions and negotiate its degree of relevance. We have based our research on a methodology linked to the ethnography of reading. From a representative sample of the narrative universes of A Song of Ice and Fire and Harry Potter, the different modes of agreed collaborative textual interpretation are explored. The data show that within these communities of practice, three reading models are developed: predictive theories in which future narrative contents are inferred; explanatory theories in which narrative arcs are endowed and charged with meaning through the analysis of canon and, finally, alternative theories with a highly creative component in which the interpretative limits of the text are explored. Within these virtual communities, hermeneutical proposals are characterized by the activation of complex, heavily referenced literary argumentation to maintain semiosis active and expand the horizon of expectations of its members.